Hak Perempuan Dalam Pembagian Harta Waris Adat Batak Toba (Studi Kasus Putusan Pengadilan No 564/PDT.G/2015/PN MDN) - Simanjuntak, Vera Waty; Latupono, Barzah; Lakburlawal, Mahrita Aprilya (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: The position of women who are not accommodated in the distribution of inheritance in the Toba Batak Customary, so the authors conducted research with the aim of finding out how women's rights are in the distribution of inheritance in the Toba Batak Customary with the Case Study of Court Decision No. 564/PDT.G/2015/PN MDN and aims to find out the basic considerations judges in deciding cases of inheritance disputes with the patrilineal family system in Adar Batak Toba.Purposes of the Research: The purpose of this study is to discuss how women's rights in the distribution of traditional Toba Batak inheritance.Methods of the Research: This research is a normative juridical research carried out using statutory, conceptual and case approaches.Results of the Research: Women's rights in the division of inheritance in the Toba Batak custom are not accommodated at all because the Toba Batak custom adheres to a patrilineal family system. In the Toba Batak tradition, it is the sons who inherit the inheritance from their parents, so that the position of girls is not respected. In Court Decision No. 564/PDT.G/2015/PN MDN is based on Article 832 of the Civil Code which equates the rights of girls and boys so as to produce fairness decisions without differentiating rights in accordance with customary law principles and provisions in positive law in matters this is the Civil Code.